2015
DOI: 10.1016/j.gheart.2014.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities for Implementation of Interventions to Prevent and Control CVD in Low-Resource Settings: A Report From CESCAS in Argentina

Abstract: In Argentina, Cardiovascular diseases are estimated to cause about 100,000 deaths and more than 250,000 coronary heart disease and stroke events annually, at a cost of more than one billion international dollars. Despite progress in the implementation of several programs to combat non-communicable diseases in Argentina over the last years, most health resources are still dedicated to infectious disease and maternal and child health. The Institute for Clinical Effectiveness and Health Policy, an independent aca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…A 2016 systematic review regarding the use of eHealth/mHealth found that minority groups, such as African Americans, are among the least underrepresented in research using such technologies for health interventions [75]. This is also observed in South American countries, considering that few studies have been conducted using eHealth/mHealth approaches to improve health outcomes associated with chronic diseases [76]. …”
Section: Discussionmentioning
confidence: 99%
“…A 2016 systematic review regarding the use of eHealth/mHealth found that minority groups, such as African Americans, are among the least underrepresented in research using such technologies for health interventions [75]. This is also observed in South American countries, considering that few studies have been conducted using eHealth/mHealth approaches to improve health outcomes associated with chronic diseases [76]. …”
Section: Discussionmentioning
confidence: 99%
“…Process evaluations nested within implementation protocols can be used to assess fidelity and quality of implementation, clarify causal mechanisms, and identify contextual factors associated with variation in outcomes (Oakley et al 2006). Evaluation of process is not a substitute for evaluation of outcomes, but it can be extremely helpful, particularly in studies with null findings, when a complex intervention can be like a black box, with uninterpretable outputs and outcomes (Rubinstein et al 2015). …”
Section: Methodsmentioning
confidence: 99%
“…In addition, the growing prevalence of diabetes mellitus across LatAm and the complexity of the disease suggest opportunities to create or strengthen collaborations towards its prevention and early detection [141][142][143][144]. For example, multinational and multidisciplinary researchpublic health-health care policy-clinical care partnerships which already exist in formal or informal platforms may be well-positioned to evaluate the impact of nutrition, health insurance, housing, and other public policies [79,141,143,[145][146][147][148][149][150][151][152][153][154] on health outcomes and assess their potential translation into preventive strategies at the public health and clinical care levels. At the same time, the eventual implementation of such strategies will be strengthened by local governments' commitment to prioritize the prevention and treatment of NCDs, in this case, diabetes, as previously voiced by experts and advocates in the region [79,141,[155][156][157][158].…”
Section: Nicaraguamentioning
confidence: 99%